It is distribution of wealth harmful for economic growth? - Flores Segovia, Miguel (Centro de Investigaciones Económicas, 2006)
It is the objective of this essay to analyse the relationship between income distribution and growth. In the first section, the central arguments of the more influential economic growth theories will be discussed. Next, the historical discussion involving the relationship between income distribution and economic growth will be outlined. Further to this I will examine the basic characteristics of models linking inequality and growth. Finally, the more recent literature regarding income distribution, social instability and economic growth will be addressed.